Narrative changes about "voices" following a contextual group therapy for people with psychosis. Issue 1 (2nd January 2021) - Langlois, T.; Bourcier, A.; Lamy, P.; Lhermine, M.; Callahan, S.; Lecomte, T.
ABSTRACT: Background: To determine the impact of a contextual group CBT intervention for voices on the narratives of people with psychosis Method: Narratives from 10 participants with psychosis and hearing auditory hallucinations, who participated in a group intervention for voices, were collected and analysed, before and after the intervention. Results: Four main themes emerged from the phenomenological analysis of the participant's narratives regarding their voices: 'representation of voices', 'explanations given to hearing voices', 'unfolding and appearance of voices, and 'reactions and emotional management of voices'. It was possible to isolate sub-categories within the four main (or superordinate) themes that evolved following the intervention, reflecting the psychological and behavioural processes at work involved in response to the voices. The identification of these processes made it possible to understand how a contextual group CBT intervention for voice management could concretely help those who receive it. Conclusion: A contextual group intervention for the management of auditory hallucinations in people with psychosis seems to improve the ability to describe, accept, and manage voices, as well as to encourage participants to relate differently, in a more peaceful way, with them.